Locked In, Locked Out : Gated Communities in a Puerto Rican City - Dinzey-Flores, Zaire Zenit (Book collections on Project MUSE., 2013)
In November 1993, the largest public housing project in the Puerto Rican city of Ponce - the second largest public housing authority in the U.S. federal system - became a gated community. Once the exclusive privilege of the city's affluent residents, gates now not only locked "undesirables" out but also shut them in. Ubiquitous and inescapable, gates continue to dominate present-day Ponce, delineating space within government and commercial buildings, schools, prisons, housing developments, parks, and churches. In this book, the author examines four communities in Ponce, showing how gates - in both physical and symbolic ways - distribute power, reroute movement, sustain social inequalities, and cement boundary lines of class and race.